Enantioselective Fluorescent Recognition of Chiral Acids by Cyclohexane-1,2-diamine-Based Bisbinaphthyl Molecules - Li, Zi-Bo (2007)
The cyclohexane-1,2-diamine-based bisbinaphthyl macrocycles (S)-/(R)-5 and their cyclic and acyclic analogs are synthesized. The interactions of these compounds with various chiral acids are studied. Compounds (S)-/(R)-5 exhibit highly enantioselective fluorescent responses and high fluorescent sensitivity toward α-hydroxycarboxylic acids and N-protected amino acids. Among these interactions, (S)-mandelic acid (10(−3) M) led to over 20 fold fluorescence enhancement of (S)-5 (1.0 × 10(−5) M in benzene/0.05% DME) at the monomer emission and (S)-hexahydromandelic acid (10(−3) M) led to over 80 fold fluorescence enhancement. These results demonstrate that (S)-5 is useful as an enantioselective fluorescent sensor for the recognition of the chiral acids. On the basis of the study of the structures of (S)-5 and the previously reported 1,2-diphenylethylenediamine-based bisbinaphthyl macrocycle (S)-4, the large fluorescence enhancement of (S)-5 with achirality-matched α-hydroxycarboxylic acid is attributed to the formation of a structurally rigidified host-guest complex and the further interaction of this complex with the acid to suppress the photo-induced electron transfer fluorescent quenching caused by the nitrogens in (S)-5.